(untitled) (Web of Teachers: Inderscience Research, 2024)
The essence of the research lies in the analysis of expressions with lexical units that actualize the category of property within the structure of a sentence-statement, selected by the method of full sampling from English-language scientific texts. To identify the semantics of lexical units, interpretative and component analysis of the lexical meaning of the examined language units is conducted.